The Protective Effect of N-Acetylcysteine on Oxidative Stress in the Brain Caused by the Long-Term Intake of Aspartame by Rats - Finamor, Isabela A. (2014)
Long-term intake of aspartame at the acceptable daily dose causes oxidative stress in rodent brain mainly due to the dysregulation of glutathione (GSH) homeostasis. N-Acetylcysteine provides the cysteine that is required for the production of GSH, being effective in treating disorders associated with oxidative stress. We investigated the effects of N-acetylcysteine treatment (150 mg kg(-1), i.p.) on oxidative stress biomarkers in rat brain after chronic aspartame administration by gavage (40 mg kg(-1)). N-Acetylcysteine led to a reduction in the thiobarbituric acid reactive substances, lipid hydroperoxides, and carbonyl protein levels, which were increased due to aspartame administration. N-Acetylcysteine also resulted in an elevation of superoxide dismutase, glutathione peroxidase, glutathione reductase activities, as well as non-protein thiols, and total reactive antioxidant potential levels, which were decreased after aspartame exposure. However, N-acetylcysteine was unable to reduce serum glucose levels, which were increased as a result of aspartame administration. Furthermore, catalase and glutathione S-transferase, whose activities were reduced due to aspartame treatment, remained decreased even after N-acetylcysteine exposure. In conclusion, N-acetylcysteine treatment may exert a protective effect against the oxidative damage in the brain, which was caused by the long-term consumption of the acceptable daily dose of aspartame by rats.